Pengembangan E-Book Interaktif pada Materi Eksplorasi Profesi Ragam Bentang Alam Wilayah Bangkalan untuk Siswa Kelas IV SDN Pejagan 5 - Emilda Shofiyah Avisenna; Izzah Fijriyah (Mataram University, 2026)
This study aims to develop an Interactive E-Book on the Material of Profession Exploration of Natural Landscapes of the Bangkalan Region for Grade IV Students of SDN Pejagan 5. Preliminary research revealed that fourth-grade students struggled to understand the connection between the natural landscapes of the Bangkalan region and the occupations of its residents, due to the lack of contextual and interactive teaching materials based on local wisdom. This situation prompted the development of an interactive e-book as a solution capable of providing a more concrete and engaging learning experience that aligns with established learning outcomes. This study uses the 4D model (Define, Design, Development, Dissemination) developed by Thiagarajan (1974), with 35 grade IV students of SDN Pejagan 5 as research subjects. The results indicate that the Interactive E-Book has been declared valid, practical, and effective. Validity was assessed by material experts (90%), learning design experts (91.6%), and teaching material experts (95%), all categorized as very valid. Practicality in limited trials reached 83.33% for teacher activity and 93.99% for student activity, while implementation trials achieved 96.65% and 96.55% respectively, both very practical. Effectiveness was demonstrated through student response questionnaires of 86% (limited trial) and 91.33% (implementation trial), with learning outcome tests reaching 100% completion in both trials.